The influence of type 2 diabetes mellitus on the frequency and complexity of ventricular arrhythmias and heart rate variability in patients after myocardial infarction - Stoičkov, Viktor; Deljanin Ilić, Marina; Stojanović, Dijana; Ilić, Stevan; Šarić, Sandra; Petrović, Dejan; Kostić, Tomislav; Cvetković, Jovana; Stojanović, Sanja; Golubović, Mladjan (Vojnosanitetski pregled, 2017)
Background/Aim. After myocardial infarction arrhythmic cardiac deaths are significantly more frequent compared to non-arrhythmic ones. The aim of the study was to investigate the influence of type 2 diabetes mellitus (T2DM) on the frequency and complexity of ventricular arrhythmias after myocardial infarction. Methods. The study included 293 patients, mean age 59.5 ± 9.21 years, who were at least six months after acute myocardial infarction with the sinus rhythm, without atrioventricular blocks and branch blocks. In the clinical group 95 (32.42%) patients were with T2DM, while 198 (67.57%) patients were without diabetes. All of the patients were subjected to the following procedures: standard ECG according to which the corrected QT dispersion (QTdc) was calculated, exercise stress test, and 24-hour holter monitoring according to which, the four parameters of time domain of heart rate variability (HRV) were analyzed: standard deviation of all normal RR intervals during 24 hours (SDNN), standard deviation of the averages of normal RR intervals in all five-minute segments during 24 hours (SDANN), the square root of the mean of the sum of the squares of differences between adjacent normal (RMS-SD), and percentage of consequtive RR intervals which differed for more than 50 ms during 24 hours (NN > 50 ms). Results. In patients after myocardial infarction, patients with T2DM had significantly higher percentage of frequent and complex ventricular arrhythmias compared to the patients without diabetes (p < 0.001). The patients with T2DM had significantly higher percentage of residual ischemia (p < 0.001), and arterial hypertension (p < 0.001), compared to patients without diabetes. The patients with T2DM had significantly lower values of HRV parameters: SDNN (p < 0.001); SDANN (p < 0.001); RMS-SD (p < 0.001), and NN > 50 ms (p < 0.001), and significantly higher values of QTdc (p < 0.001) compared to the patients without diabetes. Conclusion. The study showed that type 2 diabetes mellitus has significant influence on ventricular arrhythmias, HRV parameters and QT dispersion in patients after myocardial infarction.